2014
DOI: 10.1021/jp411488a
|View full text |Cite
|
Sign up to set email alerts
|

Cα–H Carries Information of a Hydrogen Bond Involving the Geminal Hydroxyl Group: A Case Study with a Hydrogen-Bonded Complex of 1,1,1,3,3,3-Hexafluoro-2-propanol and Tertiary Amines

Abstract: Experimental measurement of the contribution of H-bonding to intermolecular and intramolecular interactions that provide specificity to biological complex formation is an important aspect of macromolecular chemistry and structural biology. However, there are very few viable methods available to determine the energetic contribution of an individual hydrogen bond to binding and catalysis in biological systems. Therefore, the methods that use secondary deuterium isotope effects analyzed by NMR or equilibrium or k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Previous studies showed that ionization of alcohols enhances the electron density of the alcohol oxygen atom, which effectively decreases the CaÀH bond strength due to hyperconjugation resulting in normal secondary deuterium isotope effects. [55][56][57][58] Indeed, the secondary deuterium KIE on the 5' carbon atom for the model reactions are 1.15-1.2 which is near the EIE for ionization of an aliphatic alcohol (1.15) reflecting advanced leaving group bond cleavage (see the Supporting Information, Table S2). The secondary deuterium effects on the 2' carbon atom of the nucleophilic alcohol are observed to be inverse (0.85) reflecting the loss of ionization upon going from an oxyanion to a phosphoester due to advanced OÀP bond formation.…”
Section: Application To the Rnase A Enzymatic Modelmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies showed that ionization of alcohols enhances the electron density of the alcohol oxygen atom, which effectively decreases the CaÀH bond strength due to hyperconjugation resulting in normal secondary deuterium isotope effects. [55][56][57][58] Indeed, the secondary deuterium KIE on the 5' carbon atom for the model reactions are 1.15-1.2 which is near the EIE for ionization of an aliphatic alcohol (1.15) reflecting advanced leaving group bond cleavage (see the Supporting Information, Table S2). The secondary deuterium effects on the 2' carbon atom of the nucleophilic alcohol are observed to be inverse (0.85) reflecting the loss of ionization upon going from an oxyanion to a phosphoester due to advanced OÀP bond formation.…”
Section: Application To the Rnase A Enzymatic Modelmentioning
confidence: 83%
“…The success of the computational framework described here is best evaluated by the ability to identify and predict KIEs that provide insight into mechanism and, importantly, are amenable to subsequent experimental measurement. Previous studies showed that ionization of alcohols enhances the electron density of the alcohol oxygen atom, which effectively decreases the CαH bond strength due to hyperconjugation resulting in normal secondary deuterium isotope effects 5558. Indeed, the secondary deuterium KIE on the 5′ carbon atom for the model reactions are 1.15–1.2 which is near the EIE for ionization of an aliphatic alcohol (1.15) reflecting advanced leaving group bond cleavage (see the Supporting Information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…This so-called “oxy anionic substituent effect” (16, 17) leads to the acceleration of a wide range of organic reactions [such as oxyanionic [1,3] and [3,3] sigmatropic rearrangements and HAT from alkoxides (18)]. More recently, it has been shown that intermolecular hydrogen bonding between alcohols and various acceptor molecules gives rise to a similar polarization and weakening of the adjacent C–H bond (19), the strength of which is reflected in the 13 C nuclear magnetic resonance (NMR) chemical shift and the one-bond 13 C– 1 H coupling constant ( 1 J CH ) (20, 21). In particular, it was found that a 1 kJ/mol increase in the enthalpy of the H-bond resulted in a 0.2-Hz decrease in 1 J CH for hexafluoroisopropanol complexed to various amines (20).…”
mentioning
confidence: 99%
“…Hydrogen bond interactions also play crucial role in biomolecular recognition [41]. Hydrogen bond profiles between the selected molecules and the target protein DENV1 (PDB: 3L6P)…”
Section: Plos Onementioning
confidence: 99%